Kajian Teknis Metode Backfilling Dengan Cara Mekanis Pada Penambangan Timah Alluvial Di TS 1.44 Mapur Kecamatan Riau Silip Kabupaten Bangka Induk PT Timah (Persero) Tbk: Technical Study Backfilling Method By Mechanical Means On Alluvial Tin Mining In TS 1.44 Mapur, Riau Silip Village, Bangka Induk District, PT Timah (Persero) Tbk - Ryzzky, Nugrahani Trie; Mardiah, Mardiah; Akuan, Abrianto (MINERAL, 2016)
Open pit mining system for the class under TB as TS has reserves of alluvial tin, so that the postmining activities in particular using the backfilling method. Backfilling method that would be examined wasthe backfilling method by mechanial means. The study was conducted in TS 1.44 Mapur PT Timah(Persero) Tbk. Data processing to be performed was the cycle time calculation of heavy equipmentsuch as excavator, dump trucks and bulldozer using to measure time of backfilling, time of stripping,production capacity and match factor. The calculation of machine cost to calculation cost of backfilling.The measurement hole of backfilling and stripping to calculation the volume of backfilling and the volumeof overburden. Calculation time for persentage of effeciency work tools. Based on research obtainedbackfilling activities was a stage open new worked front that stripping, used the excavator loading materialinto a bath of dump truck, dumping into the hole in backfilling and leveled material used bulldozer.Backfilling volume of 171.390 m3 from pegs base and 87.000 m3 from TLR, have a difference of 84.390m3. Backfilling for 41 days with the cost of Rp 675.100.000. Stripping volume of 150.000 m3 to 63.000 m3of excess soil and stripping for 70 days. Production capacity of excavator 49.364,17 m3/month, dumptrucks 39.491,33 m3/month and bulldozer 300.249,09 m3/month. Effeciency of three equipment by0.786%. Match factor results by 72%, means unloading excavator having waiting time while dump truckwork 100%. The production of less than the maximum, so we need the add of 1 unit of dump truck so thatthe tools fit the excavator does not happen the wait time, dump trucks became to 4, it 96% or MF = 80% -100% and productifity would be maximum.